Answer:
31.2
Step-by-step explanation:
Answer:
-66
Step-by-step explanation:
-(-2)^2=-4
-3(-2)(-3)+2(-3)^3= -62
-4-62= -66
The answer is A.Use a compound interest calculator. Multiple sites to use. For me, I had to use my head for a while
(x - 2)² + (y - 6)² = 4
You can be certain about one thing just by looking at the equation (2, 6) is the center, so, obviously the circle isnt going through this point
Since the radius is 2 if we don't move from y = 6 we have points in (0, 6) and (4, 6)
So alternative b.
To be more certain just subs the point in the x and y, if its equal, it pass through
(x - 2)² + (y - 6)² = 4
To point (4, 6)
(4 - 2)² + (6 - 6)² = 4
(2²) + 0² = 4
4 = 4
Thats right
False; consider as a counterexample the function <em>f</em> : ℝ→ℝ defined by
Clearly <em>f</em> approaches -3 as <em>x</em> gets closer to -2, but neither limit from either side is equal to the function's value at <em>x</em> = 2 (that is, -3 ≠ 0), so <em>f</em> is not continuous.